A complex homozygous mutation in ABHD12 responsible for PHARC syndrome discovered with NGS and review of the literature. Issue 2 (8th June 2017) - Lerat, Justine; Cintas, Pascal; Beauvais‐Dzugan, Hélène; Magdelaine, Corinne; Sturtz, Franck; Lia, Anne‐Sophie
Abstract: PHARC syndrome (MIM612674) is an autosomal recessive neurodegenerative pathology that leads to demyelinatingP olyneuropathy, H earing loss, cerebellarA taxia, R etinitis pigmentosa, and early‐onsetC ataracts (PHARC). These various symptoms can appear at different ages. PHARC syndrome is caused by mutations in ABHD12 (α‐β hydrolase domain 12), of which several have been described. We report here a new complex homozygous mutation c.379_385delAACTACTinsGATTCCTTATATACCATTGTAGTCTTACTGCTTTTGGTGAACACA (p.Asn127Aspfs*23). This mutation was detected in a 36‐year‐old man, who presented neuropathic symptoms from the age of 15, using a next‐generation sequencing panel. This result suggests that the involvement of ABHD12 in polyneuropathies is possibly underestimated. We then performed a comparative study of other patients presenting ABHD12 mutations and searched for genotype‐phenotype correlations and functional explanations in this heterogeneous population.